1989
DOI: 10.1111/j.1365-2265.1989.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the Polycystic Ovary Syndrome: Clinical, Endocrine and Ultrasound Features in 556 Patients

Abstract: This paper reports an analysis of the clinical, endocrine and ultrasound data within a population of 556 patients with ultrasound-diagnosed polycystic ovaries. Compared with those not so affected, hirsutism was associated with a higher mean serum testosterone concentration, infertility was associated with higher mean gonadotrophin concentrations, obesity was associated with a higher mean serum testosterone concentration, hyperprolactinaemia was associated with a lower mean serum testosterone concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
170
1
15

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(200 citation statements)
references
References 31 publications
14
170
1
15
Order By: Relevance
“…Our clinical studies revealed lower serum HDL concentrations in both lean and obese women with PCOS with a negative association between insulin measurements and HDLz concentrations and a positive association between insulin and both glucose intolerance and hypertension (Conway et al, 1992). These measurements of surrogate risk markers suggested that hyperinsulinaemic women with PCOS are at a significant risk of early cardiovascular disease and clinical reports are now emerging which support this concept.…”
Section: Coronary Artery Diseasesupporting
confidence: 60%
See 2 more Smart Citations
“…Our clinical studies revealed lower serum HDL concentrations in both lean and obese women with PCOS with a negative association between insulin measurements and HDLz concentrations and a positive association between insulin and both glucose intolerance and hypertension (Conway et al, 1992). These measurements of surrogate risk markers suggested that hyperinsulinaemic women with PCOS are at a significant risk of early cardiovascular disease and clinical reports are now emerging which support this concept.…”
Section: Coronary Artery Diseasesupporting
confidence: 60%
“…Thus, there are many reports of a positive association between serum insulin and androgen concentrations in women (whh polycystic ovaries) (Burghen et al, 1980;Chang et al, 1983; but none in men. Similarly, serum testosterone concentrations are raised in obese women with polycystic ovaries (Conway et al, 1989;Kiddy et al, 1990) (with secondary hyperinsulinaemia) but reduced in men (Pasquali et al, 1991;Simon et al, 1992), reflecting low sex hormone binding globulin concentrations, as discussed below.…”
Section: Regulation Of Androgens: Differences Between the Sexesmentioning
confidence: 99%
See 1 more Smart Citation
“…50,65 Hyperandrogenism is also exaggerated in overweight women with PCOS. Hyperinsulinaemia suppresses production of SHBG by the liver, 66 leading to higher concentrations of free testosterone, but total testosterone is also positively correlated with BMI, 67,68 probably reflecting the effect of insulin on theca cell androgen production. Hyperinsulinaemia has also been implicated in the mechanism of anovulation.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios han demostrado que al menos 50% del total de pacientes con SOP presenta obesidad (1, 16,17), siendo ésta predominantemente de tipo andrógena o central, manifestándose por un índi-ce cintura/cadera aumentado (>0,85). Este tipo de obesidad se ha asociado con hiperandrogenemia, RI, baja tolerancia a la glucosa (BTG) y dislipidemia (18)(19)(20)(21). Además, se ha observado una fuerte asociación entre SOP y alteraciones metabólicas; ≈40% de las pacientes presenta BTG (15), 50% presentaría RI (2,22), y hasta un 10 a 15% presentará diabetes mellitus tipo II hacia la cuarta década de vida (23,24).…”
Section: Introductionunclassified